The impact of reconditioned orthodontic brackets on bond strength / Faisal Ismail El-Sayed Bahnasi - El-Sayed Bahnasi, Faisal Ismail (Institute of Graduate Studies, UiTM, 2018)
Introduction: Orthodontic bracket bond failure is common during orthodontic treatment. Objectives: To evaluate the Shear Bond Strength (SBS) of new orthodontic brackets, and the SBS after reconditioning and repeating the reconditioning procedure for such brackets, with and without bonding; and to evaluate the bond failure rate of new and reconditioned orthodontic brackets during orthodontic treatment. Methods: A total of 120-extracted human premolar teeth and 120 premolar stainless-steel brackets were used and were randomly divided into six groups of 20 each. Five methods of reconditioning were used in each of the first five groups while the last group was used as a control. The six groups (I-VI) were subjected to shear force for half an hour until the brackets debonded. SBS was measured and the methods showing the highest SBS were selected. Two groups were selected and then reconditioned for a second time using the previous steps. The SBS of all subgroups were examined with and without the application of a primer. For the clinical experiment, a total of 60-patients were selected from the waiting list of the orthodontic clinic of the Faculty of Dentistry, UNIVERSITY TEKNOLOGI MARA, Malaysia. The patients were randomly divided into three main groups of 20-patients each. 60-sets of 3M Unitek™ Gemini Brackets were used. The first group was reconditioned using 50μm aluminium oxide particle grit-blasting before bonding, the second group was reconditioned using the Er,Cr3+:YSGG laser and the last was used as a control group…